PARTIAL ADHERENCE WITH ANTIPSYCHOTIC MEDICATIONS AND FACTORS RELATED TO MEDICATION RELAPSE IN JORDANIAN PATIENTS WITH SCHIZOPHRENIA - Suzie Rababa’h; Nabil Alhmoud (European Scientific Journal, ESJ, 2013)
﻿Objectives and aim: Partial adherence with antipsychotic medications increases the relapse rate in patients with schizophrenia. The aim of the present study is to assess the frequency of and factors contributing to partial adherence.Method: During May 2012, psychiatrists working in a psychiatric hospital in Amman- Jordan were asked to participate in a compliance study. They were requested to evaluate the compliance of patients with schizophrenia using a questionnaire consisting of 11 questions. The frequency of unintentional and intentional partial adherence as well as patient-related factors contributing to relapse was assessed. Demographic data of participants were collected and the responses of patients were analyzed using descriptive statistics.Results: The psychiatrists regarded 74%of the evaluated patients as unintentionally partially adherent, 40% of the patients were intentionally partially adherent with medication throughout the study period. The most frequently assessed patient-related factors contributing to partial adherence were denial of illness (80%),lack of or insufficient information about their disease and medication(74.9%/73.7%),needing someone to remind them to take their medication(74.3%), side-effects related causes (64.8%), the cost of medication ( 63.1%), and long duration and complexity of regimen(60.9%).